Fetomaternal outcome in abnormal liquor volume pregnancies - Madhuri, Narra; Pal, Chayan Kumar; Sharma, Parthapratim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Variation in the amniotic fluid reflects fetal compromise, and congenital anomalies and also may predict perinatal morbidity and mortality. Methods: Singleton pregnancy subjects with well-established dates at ≥28 weeks of gestational age were taken into study. These subjects were ultrasonographically diagnosed to have abnormal liquor volumes. This study was a hospital-based single-center prospective observational study conducted in Midnapore medical college and hospital, west Bengal. The chi-square test was applied for statistical significance and a p<0.05 was considered to be significant. Results: In all subjects of abnormal liquor volume, the incidence of oligohydramnios and polyhydramnios are in the proportion of 3:1 in our study. Postdated pregnancy (28.4%), hypertensive disease (16.8%), intrauterine growth restriction (IUGR) (12.6%), and anemia (2.2%) were associated with oligohydramnios. Congenital anomalies (23.3%), GDM (16.6%), and Rh-incompatibility (3.3%) were associated with polyhydramnios. The incidence of caesarean section, meconium-stained liquor and 5-minute APGAR score <7 and NICU admission was higher in the oligohydramnios group as compared to polyhydramnios. In abnormal liquor volume, the statistical association was significant with onset of labour (p=0.00), mode of delivery (p=0.00), the colour of liquor(p-0.00), and fetal outcome (p=0.00). Conclusions: Postdated pregnancy, IUGR, and hypertensive disorders were associated with oligohydramnios and congenital anomalies, and GDM and Rh-isoimmunization were associated with polyhydramnios. In abnormal liquor volume onset of labour, mode of delivery, the colour of the liquor, and fetal outcome were significant.